2023
DOI: 10.1002/jwmg.22508
|View full text |Cite
|
Sign up to set email alerts
|

A harvest framework for a recovering American black bear population

Melanie R. Boudreau,
Mariela G. Gantchoff,
Laura Conlee
et al.

Abstract: Having reproducible and transparent science‐based processes in wildlife management ensures the integrity of decision making. These processes are particularly important when establishing harvest frameworks, as guiding information in the peer‐reviewed literature is limited. We provide an example using multiple data sets, whose products guided aspects of the development of a harvest framework for a population of recolonizing American black bears (Ursus americanus) in Missouri, USA. To characterize the spatial dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 59 publications
0
0
0
Order By: Relevance
“…Therefore, considering all factors, the overall population density of bears in the whole study area may not be much higher than that reported in other studies in different regions, and it is important to consider the seasonal concentration of bears in a certain region when calculating population density estimates [57][58][59][61][62][63][64][65]68,[76][77][78][79].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, considering all factors, the overall population density of bears in the whole study area may not be much higher than that reported in other studies in different regions, and it is important to consider the seasonal concentration of bears in a certain region when calculating population density estimates [57][58][59][61][62][63][64][65]68,[76][77][78][79].…”
Section: Discussionmentioning
confidence: 99%